PREDICTORS OF RECANALIZATION DEVELOPMENT IN PATIENTS WITH VARICOSE VEINS OF THE LOWER EXTREMITIES AFTER COMBINED PHLEBECTOMY - Черных, Константин Петрович; Кубачев, Кубач Гаджимагомедович; Казанцев, Антон Николаевич; Заркуа, Нонна Энриковна; Черных, Александр Петрович (Medicine in Kuzbass, 2020)
Purpose – a study of predictors of recanalization 2 years after combined phlebectomy (CF) in patients with varicose veins of the lower extremities (VBNA). Materials and methods. This prospective study included 151 patients with VBNA who underwent CF in the period from 2013-2017. All the studied patients were divided into two groups depending on the development of recanalization: group 1 – patients in whom recanalization occurred (41.7 %; n = 63); group 2 – patients whose recanalization did not occur (58.3 %; n = 88). Recruitment of patients was performed on an outpatient basis. Based on the results of the examination and examinations, a diagnosis was formed on the CEAP scale, on the basis of which a conclusion was drawn about the need for surgical correction. The severity of symptomatic dynamics in the postoperative period was evaluated according to the VCSS scale. The analysis of the total frequency of recanalization was carried out 2 years after the operation by calling patients to the clinic for examination and color duplex scanning. Results. As a result of the analysis, the following groups of factors became powerful predictors of the development of recanalization: 1. Clinical and demographic (female gender (p = 0.008; OR = 0.6; 95% CI = 1.284-5.511)); the presence of severe edema (p < 0.001; OR = 5.65; 95% CI = 2.561-13.363); 2. Anatomical and pathophysiological (combination of BP and occlusion (p = 0.019; OS = 2.415; 95% CI = 1.141-5.109); lesion of BPV (p < 0.001; OR = 8.816; 95% CI = 3.223-24.11). Signs of a high likelihood of developing recanalization were a number of factors of the postoperative period: 1. The need to use non-steroidal anti-inflammatory drugs (p = 0.01; OS = 4.062; 95% CI = 1.308-12.609); 2. The presence of pigmentation (p = 0.002; OS = 3.162; 95% CI = 1.511-6.616). Conclusion. Thus, in order to achieve the greatest effectiveness of the treatment with a persistent successful long-term result, contraindications to CF may include: a combination of BP and occlusion of the largest venous limb segments with severe edematous syndrome in women. Factors such as increased need for anesthesia and the formation of pigmentation in the hospital postoperative period are an important signal for monitoring the patient’s condition in the long term, in view of the high probability of disease regression.